The impact of CEO gender and educational background on capital structure - Kumala, Lucky; Suherman, Suherman; Dong, Khuu Thi Phuong (Global Advances in Business Studies, 2024)
This study aimed to investigate how CEO gender and educational background influence capital structure decisions in Indonesia. This study uses panel data from the Indonesia Stock Exchange in the 2018—2022 period. This study utilized a purposive sampling technique to obtain 335 firm-year observations. The results indicated a significant impact of CEOs from renowned universities and with high levels of education in shaping the company's capital structure. Furthermore, CEO gender does not have a significant influence on capital structure.